Research of modern advertising market in Ukraine - Поклонська, Лілія Сергіївна (Technology audit and production reserves, 2016)
Research of modern advertising market, marketing services and direct marketing in Ukraine for the period 2007-2015 and the forecast for 2016 was studied for the purpose of forming effective advertising strategy of products for industrial purposes. The following research objectives are defined: to conduct a comprehensive analysis of the media advertising market in Ukraine and its components, marketing services and direct marketing of Ukraine; to give recommendations on the use of various types of advertising products for industrial purposes. To achieve the objectives we used the following methods: analysis and synthesis, logic synthesis, analogies, comparative, monographic and graphic-analytical methods. A study of the advertising market during the period 2007-2015 was conducted. This study demonstrates the generally positive trend as for the types of media such as TV advertising, press, radio advertising, outdoor advertising, transport advertising, cinema. Decline in volumes is observed in 2014 and 2015, except indicators of Internet advertising that increases in 2015. The research of marketing services in Ukraine during the period 2007-2016 was conducted. There is the negative dynamics in all types of marketing services, except the programs that help increase sales here and now, to increase the loyalty of existing customers, that is, trade marketing and loyalty marketing. The volume of direct marketing was analyzed and it can be concluded that the dynamics is negative. It is associated with significant economic and political instability. In 2016 it is projected that direct marketing that generating sales will improve its performance, but image direct marketing will continue to decrease. The recommendations on the feasibility of using channels of advertising for products for industrial purposes, such as TV advertising, radio advertising in specialized magazines and newspapers and online advertising in collaboration for more effective impact on the target audience.